Primitive transcendental functions and symbolic computation. (July 2018) - Navarro Guevara, Douglas
Abstract: This paper presents the theoretical support for a novel and efficient approach to represent and deal symbolically with an important ensemble of complex functions. These functions are characterized by a Maclaurin series expansion whose general term may be factoring as: b j T j + k x j j ! where b j is periodic, k ∈ Z and T m is a complex sequence that characterizes a family of functions. The functions are structured in families of Euclidean vector spaces that facilitate a discrete vector representation. The used representations provide important facilitates for the symbolic computation of divers operators/operations that are executed by the computation of their " dual counterparts " into the representation space.